INOVASI PRODUK PADA USAHA NARASA POTATO DALAM MENGATASI PERSAINGAN DI INDUSTRI KREATIF - Maikel Romy Rambunga; Suryadi Samudra; Harnida Wahyuni Adda (PT Naureen Digital Education, 2023)
Indonesia's economy is largely driven by increasing household consumption and one of the fast-growing industries is the food and beverage industry Researchers conduct research on innovation strategies that can be carried out in an effort to influence the development of Narasa Potato's sales production. Therefore, the purpose of this study is to analyze what innovation steps can significantly affect business development and analyze the position of the ongoing business and formulate innovations that need to be done to overcome existing problems. Based on the problems that occur in the Narasa Potato business, the purpose of this study is to formulate an innovation strategy that can be used in the development of the Narasa Potato business.